2022
DOI: 10.1007/s43762-022-00038-x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of suitable landfill site selection for municipal solid waste management by GIS-based MCDA technique in Siliguri municipal corporation planning area, West Bengal, India

Abstract: Identification of suitable landfill sites for urban wastes with ease and economic benefits in the metropolitan area is a complex task. Most of the developing countries consider wastelands outside of the urban areas are the ideal places to dispose of urban wastes. Landfill site selection is an essential planning procedure that helps to avoid environmental concerns such as water contamination, public health degradation caused by unsanitary landfills. So, employing a geographic information system (GIS) and multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…To accurately assess land values, a survey was conducted utilizing GPS technology to pinpoint precise values across different locations within the study area. This survey gathered x and y coordinates (latitude and longitude) to generate a spatial map, employing the Inverse Distance Weighting (IDW) tool within the ArcGIS platform [42,65]. Through a combination of primary surveys conducted with local residents and insights from secondary sources, it was determined that land valuation in the vicinity of prime downtown area or a bit distance of town central business district (CBD) point ranges from 0.80 lakhs to 11.65 lakhs per Katha which is depicted in Fig.…”
Section: Land Valuementioning
confidence: 99%
“…To accurately assess land values, a survey was conducted utilizing GPS technology to pinpoint precise values across different locations within the study area. This survey gathered x and y coordinates (latitude and longitude) to generate a spatial map, employing the Inverse Distance Weighting (IDW) tool within the ArcGIS platform [42,65]. Through a combination of primary surveys conducted with local residents and insights from secondary sources, it was determined that land valuation in the vicinity of prime downtown area or a bit distance of town central business district (CBD) point ranges from 0.80 lakhs to 11.65 lakhs per Katha which is depicted in Fig.…”
Section: Land Valuementioning
confidence: 99%
“…Studies between 1990 and 2004 show that MCDA and GIS usage has grown (Malczewski, 2006). When this situation comes to 2022, a perfect match is seen by adding the fuzzy feature which is frequently encountered in conformity analysis (Beshr et al, 2022;Hagos et al, 2022;Raad et al, 2022;Roy et al, 2022).…”
Section: Analytic Hierarchy Process In Multi Criteria Decision Analysismentioning
confidence: 99%
“…Finally, the map of the final weighting factors of suitability for MSWLF was prepared and classified into four classes. Roy et al (2022), in a study using GIS and MCDA, investigated and found a suitable landfill in Bengal, India.…”
Section: Introductionmentioning
confidence: 99%